Extracting turkey coronaviruses from the intestinal lumen of infected turkey embryos yields full genome data with good coverage by NGS. Issue 3 (4th May 2022) - Flageul, Alexandre; Courtillon, Céline; Allée, Chantal; Leroux, Aurélie; Blanchard, Yannick; Deleforterie, Yves; Grasland, Béatrice; Brown, Paul Alun
ABSTRACT: Currently, turkey coronaviruses (TCoV) are isolated from homogenized intestines of experimentally infected embryos to ensure a maximum recovery of viral particles from all components of the intestines. However, the process of homogenization also ensures release of a significant amount of cellular RNAs into the sample that hinders downstream viral genome sequencing. This is especially the case for next generation sequencing (NGS) which sequences molecules at random. This characteristic means that the heavily abundant cellular RNA in the sample drowns out the minority viral RNA during the sequencing process and, consequently, very little to no viral genome data are obtained. To address this problem, a method was developed, in which 10 descendent isolates of the European strain of TCoV were recovered uniquely from the intestinal lumen without homogenization of the tissue. For nine out of 10 samples, NGS produced viral RNA reads with good coverage depth over the entire TCoV genomes. This is a much-needed new, simple and cost effective method of isolating TCoV that facilitates downstream NGS of viral RNA and should be considered as an alternative method for isolating other avian enteric coronaviruses in the interest of obtaining full-length genome sequences.